Triggers of phytoplankton bloom dynamics in permanently eutrophic waters of a South African estuary. Issue 3 (25th September 2018) - Lemley, DA; Adams, JB; Strydom, NA
Abstract : The permanently eutrophic Sundays Estuary experiences recurrent harmful algal blooms (HABs) of Heterosigma akashiwo (Raphidophyceae). This study aimed to identify the environmental variables shaping phytoplankton community composition and succession patterns during a typical spring/summer harmful algal bloom (HAB) period. Monitoring of abiotic and phytoplankton variables was undertaken over the period of a month in 2016. Surface water salinity corresponding to mesohaline conditions (9 to 12) was a prerequisite for site selection. During the study, two HABs (>550 µg Chl a l −1 ) of H. akashiwo occurred, each lasting for approximately a week in duration. Analyses highlighted nutrient depletion (i.e. nitrate and phosphate concentrations) as the key constraint on bloom duration. When the density of H. akashiwo decreased, the community composition became more diverse with species belonging to Bacillariophyceae and Dinophyceae becoming more abundant; albeit to a lesser degree (<180 µg Chl a l −1 ). Dissolved oxygen shifted from super-saturated conditions (>14 mg l −1 ) during peak HAB conditions, to instances of bottom water oxygen depletion (2–4 mg l −1 ) during the decay phase. These findings highlight the potential severity of transforming a catchment from natural to one that is highly regulated by agricultural practices, while also emphasising the need for management intervention.